<htm>Description of a new species of Opisthacanthus Peters (Scorpiones: Hormuridae) from Suriname/Brazil border with some biogeographic considerations </htm> - Lourenço, Wilson R. (Acta Biológica Paranaense, 2017)
<htm>Description of a new species of Opisthacanthus Peters (Scorpiones: Hormuridae) from Suriname/Brazil border with some biogeographic considerations </htm>